Côte d'Ivoire's elusive quest for peace - Arnim Langer (University of Bath, Centre for Development Studies (CDS), 2010)
The October 2010 elections in Côte d'Ivoire were supposed to bring lasting peace to a country that has been split since a rebellion of predominantly northern forces in September 2002. Instead, disagreement over the electoral results has pushed the country back to the brink of civil war. The Ivorian electoral debacle adds to the long list of failed peace agreements and initiatives that have been undertaken since the 2002 violent rebellion. The main objective of this paper is to analyse why restoring peace and stability in Côte d'Ivoire has proved to be so difficult. On the basis of this analysis, it will be shown that the Ivorian electoral debacle should not have come as a surprise because the same dynamics and factors that were responsible for the failure of previous peace agreements and initiatives are again at play.
Keywords: 330; Öffentliche Sicherheit; Frieden; Wirtschaftlicher Wiederaufbau; Wahl; Elfenbeinküste